CROSS-BORDER SERVICE OF DOCUMENTS IN EU GOING ONLINE: IMPLEMENTATION AND IMPLICATIONS (EU and comparative law issues and challenges series (ECLIC), 2023)
The service of documents is crucial for the smooth initiation and operation of cross-border civil and commercial proceedings. Cross-border service of documents raises the issues on effectiveness and efficiency of proceedings together with the effective right to access a (foreign) court in terms of the language used and the effective possibility of appearing before a court. In response, international judicial cooperation in the service of documents was established and operated for decades, starting with the Hague 1965 Service Convention. The importance of proper service of documents also comes from the fact that it is a condition to recognise and enforce the final foreign judgment in different domestic, European, and international legislations. The abolition of the exequatur procedure in the context of the EU legislation in civil matters points toward an even greater need for harmonisation, which seeks to be achieved through the Service of Documents Regulation. The changes in individual lives and business operations affected by digitalisation have also led to the need for the modernisation of judicial cooperation. The Service of Document Regulation underwent the recast procedure and entered into force on 1 July 2022. It has brought novelties, given the introduction of mandatory electronic communication between the agencies and facilitating electronic and direct service. The significant changes concern the e-Codex as the mean of communication; electronic service; electronic signature of deeds, documents and forms; and assistance in address enquiries. The paper assesses the implication of using ICT in the service of documents and, at the same time, addresses whether the changes are fully up with the fast-growing general technological advancement since it seems that the implementation level still depends on the Member States.